Enhancing Intrinsic Motivation in Higher Education Case Study: University Student in Labuhanbatu - Zarkasih, Amron; Munthe, Rika Syahmewah; Wahyuni, Erni; Mandili, Irhamna (International Journal of Educational Research & Social Sciences, 2022)
Intrinsic motivation is known as the most influential motivation compared to other types of motivation, because intrinsic motivation comes from within a person without any external intervention, so that activities carried out with intrinsic motivation will be carried out continuously with feelings of pleasure and deep focus. when doing it. If it is associated with the context of the world of education, it is very important for students to have intrinsic motivation when learning. Based on previous research, it was found that students who are intrinsically motivated have good academic achievements compared to students who do not have intrinsic motivation. Seeing the importance of the role of intrinsic motivation, this study wanted to examine variables that have a connection with the world of education on the emergence of intrinsic motivation. This study uses quantitative methods and uses an online questionnaire in collecting data. The sample in this study were students who were in Labuhanbatu district, North Sumatra. The selected sample criteria were students who underwent online learning methods during the COVID-19 pandemic. Researchers set the sample criteria because the transition from offline to online learning systems certainly disrupts student engagement with offline learning systems, so it is necessary to restore student engagement in post-covid-19 offline learning.